Profiles of dual language education in the 21st century - Arias, M. Beatriz; Fee, Molly 1986- (Bristol Multilingual Matters, 2018)
"In the last 20 years dual language education programs have increased in number and expanded in range, spanning pre-K through high school. This book examines the key attributes of successful dual language programs, as well as the challenges and opportunities involved in extending the dual language instructional model to pre-K and secondary settings"--Provided by publisher.
Dual language programs -- Recent research on the three goals of dual language education / M. Beatriz Arias and Amy Markos -- Legacy programs : Key Elementary, Arlington, Virginia / Igone Arteagoitia -- Dual language bilingual education in NYC : a potential unfulfilled? / Ofelia Garcia, Kate Menken, Patricia Velasco, and Sara Vogel -- Elgin, Illinois : an entire district goes dual : the journey of a district committed to culturally and linguistically responsive instruction / Wilma Valero and Patricia Makishima -- Implementing dual language : programmatic issues -- Implications of research for dual language at the early childhood level / Kathryn Lindholm-Leary -- Opportunities and dilemmas for TWI programs at the secondary level / Carol I. Bearse, Ester J. de Jong, and Min-Chuan Tsai -- Teacher preparation for dual language classrooms / Barbara Kennedy -- Making space for dual language education : the role of policy / Donna Christian -- Conclusion : taking stock : lessons on dual language education / Fred Genesee.
Includes bibliographical references and index.
Keywords: Education, Bilingual -- United States; Multicultural education -- United States; Education, Bilingual -- United States -- Case studies; Multicultural education -- United States -- Case studies